Clarifying the relationships between institutions and global strategy. (17th May 2019) - Cuervo‐Cazurra, Alvaro; Mudambi, Ram; Pedersen, Torben
Abstract: Research summary : We review the relationships between institutions and global strategy and explain several clarifications for future research. First, studies need to clarify the standard used to assess quality in institutional dimensions they research rather than let readers assess them from the measures. Second, analyses need to specify the theoretical approach used, which may be based on the paradigm from a single discipline (economics, sociology, politics, psychology) or the integration of underlying disciplines, as often seen in management. This must form the basis of a consistent set of assumptions rather than a potpourri of arguments from incompatible logics. Third, investigations need to clarify the direction of relationship and mechanisms. On the one hand, studies on the impact of institutions on strategy should clarify the institutional influences used (adapt, appeal, avoid). On the other hand, research on the effect of strategy on institutional change should clarify the institutional strategies (inform, influence, incentivize) and institutional spillovers (compete, command, copy) by which firms change institutions. Managerial summary : The study of institutions (controls of the behavior of individuals and firms) has become a popular topic analyzed in global strategy. Unfortunately, there is some confusion on how institutions affect the global strategy of firms because of differences in the viewpoints used to explain the relationships. We clarify past arguments by explaining the need to identify the standards used to assess quality in institutions, and the assumptions of approaches based on underlying disciplines (economics, sociology, politics, or psychology) as well as those that integrate these disciplines like in management. We also explain the mechanisms by which institutions affect the global strategy of firms (adapt, appeal, avoid), as well as the mechanisms by which global strategies influence the transformation of institutions via institutional strategies (inform, influence, incentivize) and institutional spillovers (compete, command, copy).